In Search Of. - HALTER, ED (Artforum International, 2014)
The article focuses on computer programmer and artist Guthrie Lonergan. The author explores one of Lonergan's earliest works titled "Lonely Los Angeles," which depicts screenshots of Los Angeles, California from the Internet web mapping service MapQuest. He discusses Lonergram's integration of digital media and art and examines how his work has evolved as social media has changed.